Pós-Dipping, na produção, composição e qualidade do leite. - Alves, Elizabeth Simões do Amaral (2017)
The objective of this study was to evaluate the influence of post-dipping on the production, composition and quality of milk in cows positive for subclinical mastitis from two crosses (++), in two farms located in Camaragibe-PE and Craíbas-AL in the northeastern region of Brazil. The experiment consisted of data collection in two moments: time I, before the hygienic management of the milking was implemented, where the post-dipping technique was not used as a control program. Time II, after training and implantation of the hygienic management of the milking, practicing the post-dipping with the use of iodine based disinfectant, in the concentration of 0.5%. The results of the means and standard deviation of the analyzes of a total of 305 milk samples from two farms were studied, evaluating the effect of post-dipping on the variables studied: CCS, CMT, Fat, Protein, Lactose, Total Solids, Non-Fat Solids, weighing (kg) and microbiological yield, in two stages, before and after the implementation of the post-dipping practice. The statistical analysis used a completely randomized experimental design and arranged in plots subdivided in time, with two collections corresponding to the plots and two farms the subplots, the collected data were submitted to analysis of variance (ANOVA) p≤0.05 by the F test in the software Sisvar 5.6. The post-dipping practice during 30 days resulted in the means and standard deviation of the analyzes of the studied variables, where there was a decrease in CCS, CMT and microbiological score profile in both farms, statistically significant values (p≤ 0.05). The highest etiological agent found was Staphylococcus spp. The fat and lactose profile increased in both farms, but there was no significant difference (p≥0.05). Protein increased in both farms, but in farm 1, there was no significant difference (p≥0.05) and in farm 2, there was a significant difference (P≤0.05). Total Solids, NFG and weighing had a percentage increase, but the means of weight did not differ statistically (p≥0.05). Post-dipping is an effective measure in the control of subclinical mastitis and brings health benefits to the mammary gland, improves the quality of the raw material, prolongs the shelf life of the derivatives and reduces risks to public health.